PENGARUH POLARITAS PADA KEKERASAN DAN STRUKTUR MIKRO LAS SMAW MATERIAL ST 40 ELEKTRODA E 6013 - Fande Febrian N. F; Paridawati -; Supriyanto Wibowo (Jurnal Ilmiah Teknik Mesin, 2018)
The welding process on the steel causes mechanical properties such as residual stress and poorpenetration, this is because it can be caused by the use of polarity in welding because the theory forpolarity use is adjusted to the materialto be welded, thisresearch aims to know the the effect ofpolarity on ST 40 plate steel material with electrode E 6013. This method uses two methods ofwelding the first straight and second polarity method using reverse polarity method using reversepolarity method using ST 40 steel material (60 mm x 27,5 mm x 10 mm), then using hardnesstesting and microstruktur testing. The result of the research and calculation of known highhardness value 148,67 HR and for microstructure test result there is ferrite and perlite microstructure on raw material, and for welding area and HAZ grain area become more smooth due tohigh heat exposure so that the structure becomes finer, and the structure is formed ferrite andperlite with accicular ferrite lines. This to solve the problem when it is cracked or broken at thewelding area on the component convenyor between axle connecting with drive roll can be causeddue to incorrect use of polarity.